-74=n+17

Simple and best practice solution for -74=n+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -74=n+17 equation:



-74=n+17
We move all terms to the left:
-74-(n+17)=0
We get rid of parentheses
-n-17-74=0
We add all the numbers together, and all the variables
-1n-91=0
We move all terms containing n to the left, all other terms to the right
-n=91
n=91/-1
n=-91

See similar equations:

| 70+r=82 | | 15*x=225 | | |3w-4|=|3w-5| | | 5*x=225 | | 10x=35-5x | | 4r-18r=42 | | (3/4)x=2/3 | | (3/4)x-(2/3)=0 | | 6x-3=3-7x | | 4(2x-3)=(3+8x)-11 | | 6x^-15x+36=0 | | 7n-14=2n+6 | | 25+7x+5x=1 | | 7w=4w-21 | | 56x=896 | | 3x-4+7x=14 | | 6x^+18x+12=0 | | 6x^-18x+12=0 | | x=4,8,12,20,x,52 | | 45=x-5 | | 45=x- | | x+.13x=29320000 | | 5y-16=3y=20 | | |15-4y|=0 | | (x+5)/(x-5)=0 | | m-3(2m-5)-1=14 | | X+14=12/x+2 | | 0.04*0-18y=7 | | 146=x(x+1)(x+3) | | 5/24/14/3=x/7/6 | | 6-4(3x-1)=-4 | | 6-4)3x-1=-4 |

Equations solver categories